Perspectives and practices of parents on young children’s household task participation - Bueno, Maria Isabel G.; Molbog, Anica Siesta I.
This study investigates the perspectives and practices of parents regarding the household task participation of young children, specifically aged 3 to 4 years old. Anchored in Vygotsky’s Sociocultural Theory and Rogoff’s concept of guided participation, the research examines how cultural beliefs and parental attitudes influence children engaging at home in three identified categories of household tasks— self-help, self-care, and family care. Having a qualitative research design, data were gathered through an in-depth interview assisted by a checklist survey to effectively draw out the experiences of 23 parents whose children are enrolled at U.P. Child Development Center as participants. Findings indicate that parents observed their young children participating in self-help, self-care, and family care tasks at home. Young children showed greater independence when participating in self-help and self-care tasks; on the other hand, they require utmost guidance when engaging in family care tasks. Meanwhile, parents acknowledge the importance of household task participation in fostering responsibility, independence, cooperation, and overall holistic development, their actual practices vary widely. Some parents actively involve their children in chores they deem age-appropriate, seeing these as valuable learning opportunities. Others, however, tend to exclude their children from such responsibilities, often due to a strong emphasis on academic activities and structured schooling. This variation highlights a broader tension between fostering independence at home and prioritizing structured learning outside it. The study advocates for greater recognition of young children as capable contributors at home and encourages parenting practices that support their early developmentally appropriate involvement in everyday tasks.